2011
DOI: 10.1007/s11095-011-0507-5
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Pharmacokinetic Study Using T1 Mapping and Gd-Chelate- Labeled Polymers

Abstract: Purpose Recent advances in drug discovery have led to the development of a number of therapeutic macromolecules for treatment of posterior eye diseases. We aimed to investigate the clearance of macromolecular contrast probes (polymers conjugated with Gd-chelate) in the vitreous after intravitreal injections with the recently developed ms-DSEPI-T12 MRI and to examine the degradation of disulfide-containing biodegradable polymers in the vitreous humor in vivo. Methods Intravitreal injections of model contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…54 By using MR imaging, the authors calculated the half-life using T1-mapping. They followed the contrast agents for approximately two days, showing the feasibility of using the noninvasive technique of MRI in monitoring the biodistribution and clearance of the macromolecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 By using MR imaging, the authors calculated the half-life using T1-mapping. They followed the contrast agents for approximately two days, showing the feasibility of using the noninvasive technique of MRI in monitoring the biodistribution and clearance of the macromolecules.…”
Section: Discussionmentioning
confidence: 99%
“…They followed the contrast agents for approximately two days, showing the feasibility of using the noninvasive technique of MRI in monitoring the biodistribution and clearance of the macromolecules. 54 Altogether, the half-life of SPION varies considerably depending on the formulation and coating.…”
Section: Discussionmentioning
confidence: 99%
“…Short retention of free drug in the anterior chamber typically occurs due to the aqueous humor turnover and clearance system (rate ≈0.18 mL h −1 ) . Therefore, it is highly desirable to investigate whether only 5% of total dose released from delivery carrier during the later follow‐up time points (day 20–day 84) is sufficient to reach therapeutic drug level (i.e., >10 µg mL −1 ) in the ocular anterior chamber.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, MRI was not able to visualize the clearance pathways from the subconjunctival space, except an increase in the contrast signal at the buccal lymph node, possibly due to the contrast agent concentration in and the dimensions of the blood and lymph vessels 2. In MRI studies of intravitreal injection4,8,9 and intraocular implant,2,11 contrast agents were not detected at the level that can be quantified in the anterior chamber with the MRI techniques. There was also no identifiable elimination pathway from the vitreous after intravitreal administration, probably due to the limitations of the MRI studies as described above.…”
Section: Introductionmentioning
confidence: 93%
“…Magnetic resonance imaging (MRI) is a noninvasive method and can be used to study the mechanisms of ocular drug delivery. Previous studies have demonstrated the utility of MRI to characterize the routes of penetration and ocular barriers such as the dynamic barriers, least resistive route of transscleral penetration, drug delivery flux‐enhancing mechanisms, locations of periocular and intraocular depots, and release kinetics from these depots (or ocular implants) in periocular, intrascleral, suprachoroidal, and intravitreal delivery 2–10. Such information would be difficult to obtain in traditional pharmacokinetic studies involving the dissection of the eye in ocular delivery research.…”
Section: Introductionmentioning
confidence: 99%